MANFAAT SKORING PROGNOSTIK DALAM PENENTUAN TATA LAKSANA KASUS METASTASIS OTAK - Yunni Diansari (PERDOSNI, 2019)
CLINICAL UTILITY OF PROGNOSTIC SCORES TO GUIDE THE MANAGEMENT OF BRAIN METASTASESABSTRACTMetastatic brain tumors are the most common intracranial neoplasms in adults and associated with significant morbidity and mortality. The current therapeutic options include surgery, whole brain radiation therapy (WBRT), stereotactic radiation (SRS), systemic therapy and symptom management only. The goals of brain metastasis management are giving longer survival, if possible the improvement in neurologic deficit and a better quality of life. Prognostic scores, a useful tool for BM patients, as an estimation of a patient’s prognosis can guide the tailored treatment for these patients. A more aggressive approaches is recommended in patients with good performance state with and controlled systemic disease. While palliative management is focused to patients on terminal state or with other comorbid disease. A number of prognostic scoring systems for BM patients have been proposed are Recursive Partitioning Analysis (RPA), the Score Index for Radiosurgery (SIR), the Basic Score for Brain Metastases (BSBM) and the Graded Prognostic Assessment (GPA). Recursive Partitioning Analysis and GPA are able to be implemented in brain metastatic patient in Indonesia.Keyword: Brain metastatic, prognostic scores, survival rateABSTRAKTumor otak metastasis merupakan tumor intrakranial yang paling sering dijumpai dan menyebabkan morbiditas serta mortalitas yang bermakna. Pilihan tata laksana terdiri dari tindakan bedah, whole brain radiation therapy (WBRT), sterotactic radiosurgery (SRS), terapi sistemik atau tata laksana simtomatik saja. Tujuan tata laksana pada pasien dengan metastasis otak adalah memperpanjang survival jika memungkinkan dengan mengontrol defisit neurologis dan memberikan kualitas hidup yang baik. Skoring prognostik merupakan metode yang bermanfaat pada kasus metastasis otak, karena dengan dapat memperkirakan prognosis pasien maka dapat menentukan pilihan tata laksana yang tepat. Tata laksana agresif direkomendasikan pada penderita dengan status performance yang baik dan penyakit sistemik yang terkontrol. Adapun tata laksana paliatif ditujukan pada pasien dengan kondisi terminal atau ada komorbid lain yang menyertai. Beberapa skoring prognostik telah diajukan seperti, Recursive Partitioning Analysis (RPA), Score Index for Radiosurgery (SIR), Basic Score for Brain Metastases (BSBM), dan Graded Prognostic Assessment (GPA). Recursive Partitioning Analysis dan GPA merupakan pilihan yang dapat diterapkan pada populasi pasien metastasis otak di Indonesia.Kata kunci: Metastasis otak, skoring prognostik, survival rate